Fonons ópticos e propriedades dielétricas intrínsecas de NaTaO3 policristalino e de fibras monocristalinas de CaTa2O6 e CaNb2O6 - Nayara Gomes Teixeira (2012)
This work has provided an ceramic dielectric: the sodium tantalate (NaTaO3) characterize it by X-ray diffraction to study the behavior of its optical phonons by Raman and Infrared spectra. The study of NaTaO3 by Raman spectroscopy was done at different temperatures (up to 913 K), where we observe a systematic reduction in the number of bands with increase of the temperature consistent with the sequence of phase transitions of this perovskite center-symmetrical. Using infrared spectroscopy, it was possible to obtain a spectrum of the material and adjust it with the method based on semi-quantum model of the four parameters. This spectrum allowed us to obtain the dielectric permittivity was 52.2 and the quality factor × around 10.9 THz. Other two ternary oxides were addressed in this study: calcium niobate and calcium tantalate single crystal fibers (CaNb2O6 e CaTa2O6), obtained by growth by laser fusion. These fibers, micrometric dimensions were oriented by X-ray diffraction and investigated by Raman and Infrared spectroscopies. It is worth noting the pioneering of our work on the use of microscopy in the far infrared region. The calcium niobate presents orthorhombic structure whose space group is Pbcn. Our calculations predict 54 allowed bands to the Raman spectra with were determined using different scattering configurations. We verified the presence of 34 modes in the infrared spectroscopy of the 38 predicted by the group theory of for this structure. We obtained the values of the dielectric constant of = 18.2 and quality factor < × > of 185 THz. For the calcium tantalate was determined thirteen of the sixteen modes planned for the infrared and Raman modes all 21 predicted by the theory group for its cubic polymorph ordered. We obtained the dielectric constant and quality factor, respectively = 31.7 and × = 20.5 THz, ensuring thus the suitability of these materials for applications in optics and microwaves.